The Regulatory Status Analysis for Updating the Public Legal Awareness on Human Rights in Indonesia - Mulyono, Andreas Tedy; Pramono, Rudy (Badan Strategi Kebijakan Hukum, 2022)
This study contends that quantitative empirical legal research is instrumental in enhancing comprehension of public legal awareness regarding the implementation of human rights protection in Indonesia. Utilizing Partial Least Squares-Structural Equation Modelling (PLS-SEM), the study offers a flexible framework to explore the relationship between human rights ideals and key elements of the legal system as research variables. This research constitutes a literature review emphasizing the significance of empirical quantitative methods, particularly through the development of a path model termed Regulatory Status Analysis. In the proposed model, justice, certainty, and expediency are posited as independent variables representing fundamental legal ideals, while substantive law and legal structure serve as mediating variables within the legal framework. Through empirical testing, the path model elucidates the intricate connections among these variables, focusing on their impact on public awareness and compliance with legal norms safeguarding human rights. Findings indicate that substantive law significantly enhances awareness of legal obligations, whereas the influence of legal structure is minimal, possibly due to perceived inadequacies in enforcing laws against human rights violations. These empirical insights underscore the imperative of developing a robust human rights legal framework conducive to effective implementation and enforcement. By informing national and global legal scholarship, this research aims to guide policy-makers in refining legal systems that promote public awareness, compliance, and protection of human rights.